Innovative Multicompartment Bathman as an Alternative Basin to Common Bed Bath Provisions: An Evaluative Comparative Study - Madayag, Rudena; Tayao, Mary Madeleine; Carlos, Leahna Joyce; Castro, Dianne Nicole; Espinosa, Kurt Sebastienne; Gallego, Maria Julianne; Lalic, Alijah Edel; Lat, Nazareil; Lazaro, Mykyla Sheyn; Santos, Sean Caleb; Sicat, Keith Angela; Mallari, Jonel (MALATA SAINS INDONESIA, 2025)
Introduction: With traditional bed bath (TBB) posing time management challenges and disposable wet wipes (DWW) raising environmental concerns, there is a need to explore innovative solutions. Objective: The researchers aimed to assess Innovative Multicompartment BathMan (IMB) compared to TBB and DWW, focusing on convenience, time-saving, and cost-effectiveness, addressing existing gaps in bed bath practices and advancing patient care delivery. Method: A descriptive evaluative comparative design was employed, with 30 registered nurses from a hospital in Angeles City, Philippines as respondents. Data were collected using a modified 5-point Likert scale questionnaire with 7 statements on bed bath methods' convenience, time-saving, and cost-effectiveness. Statistical analysis was conducted using descriptive statistics and the Kruskal-Wallis H test. Ethical clearance was obtained from the university ethics board before data collection. Results: Analysis revealed IMB (x̄=3.53) as more convenient compared to TBB (x̄=3.44) and DWW (x̄=3.26). In terms of time-saving, IMB (x̄=3.47) was favored over DWW (x̄=3.45) and TBB (x̄=3.02). While TBB (x̄=3.88) emerged as the most cost-effective method in contrast to IMB (x̄=2.7) and DWW (x̄=2.48). Cost-effectiveness ratings were generally positive across all methods (p-value=<.001). When it comes to convenience, supplies, and effort of use revealed a significant difference among the methods (p-value ≤.050). Conclusion: The study addressed gaps in bed bath practices by enhancing nursing workflows with IMB to make bed baths more convenient and reduce time. The researchers suggested expanding future research to multiple healthcare facilities and a more diverse sample for better generalizability. Healthcare institutions should consider integrating IMB to optimize nursing efficiency and patient outcomes.